PENGARUH CITRA MEREK TERHADAP LOYALITAS KONSUMEN PRODUK SEPATU MEREK VANS DI KOTA PALU - Awliyah Kartini, Risqi (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2018)
Independent variables used in this study are corporate image, user image, product image, while the dependent variable is consumer loyalty. The type of research used in this research is descriptive causal method. The sample used in this research is as much as 80 respondents with the form of sampling using purposive sampling technique. Data analysis method used in this research is multiple regression method. The results showed that the brand image consisting of corporate image, user image, and product image influence on consumer loyalty.